Toward glycerol biorefinery: metabolic engineering for the production of biofuels and chemicals from glycerol - Chen, Zhen (Biotechnol Biofuels, 2016)
As an inevitable by-product of the biofuel industry, glycerol is becoming an attractive feedstock for biorefinery due to its abundance, low price and high degree of reduction. Converting crude glycerol into value-added products is important to increase the economic viability of the biofuel industry. Metabolic engineering of industrial strains to improve its performance and to enlarge the product spectrum of glycerol biotransformation process is highly important toward glycerol biorefinery. This review focuses on recent metabolic engineering efforts as well as challenges involved in the utilization of glycerol as feedstock for the production of fuels and chemicals, especially for the production of diols, organic acids and biofuels.